Strontium-injected titanium-based bone biological material as well as preparation method and application thereof

By constructing the Sr@PTL coating on the surface of titanium-based dental implants, the problem of insufficient bone binding of titanium-based implants is solved, and bone immunomodulation and bone dysfunction are achieved through the continuous release of strontium ions and the polarization of macrophages. The improvement of regeneration effect simplifies the surface modification process and is suitable for industrial production.

CN119303162APending Publication Date: 2025-01-14THE FIRST MEDICAL CENT CHINESE PLA GENERAL HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310862934.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing titanium-based dental implants lack bioactivity and effective osseobin capacity, resulting in loosening and premature failure of the implant, and the existing surface modification methods are complex and inconvenient for industrial production.

Method used

By mixing lysozyme with strontium acetate and using tris(2-carboxyethyl)phosphine (TCEP) for phase transformation, Sr@PTL coating was constructed on the titanium surface to achieve continuous release of strontium ions and M2 polarization of macrophages. Regulates the inflammatory environment to promote bone regeneration.

Benefits of technology

It has achieved the improvement of bone immunomodulation performance of titanium-based bone biomaterials, promoted the expression of anti-inflammatory factors and bone healing factors, enhanced bone regeneration capabilities, and simplified the surface modification process, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303162A_ABST
    Figure CN119303162A_ABST
Patent Text Reader

Abstract

The invention provides a strontium-injected titanium-based bone biological material and a preparation method and application thereof, and belongs to the technical field of biological materials.The preparation method comprises the following steps that a TCEP buffer solution and a strontium-doped lysozyme solution are mixed, and a strontium-doped lysozyme coating is obtained; and coating the strontium-doped lysozyme on the surface of the sterile titanium sheet for reaction, washing with a PBS buffer solution, and carrying out vacuum drying to obtain the strontium-doped lysozyme titanium sheet. The Sr (at) PTL coating is constructed on the surface of titanium through chelation of phase transformation lysozyme and strontium ions, the strontium-injected titanium-based bone biological material can continuously release the strontium ions, has a good inflammation inhibition effect, can induce M2 phase polarization of macrophages cultured on the surface of the material, promotes the macrophages to secrete bone healing related factors, and has a good application prospect. According to the present invention, the macrophage can be used to regulate the local inflammation environment, the differentiation of the macrophage M2 phase is regulated to shape the immune microenvironment beneficial to osteogenesis so as to promote the bone regeneration, and the good biocompatibility is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a strontium-injected titanium-based bone biomaterial and a preparation method and application thereof. Background Art

[0002] Implantable biomaterials, such as dental implants, have been well-established in the restoration of lost teeth. However, inflammatory loosening of implants due to insufficient osseointegration between the implant surface and the host bone tissue is the main cause of implant failure. With this in mind, the current design paradigm for implantable biomaterials focuses on regulating the physicochemical properties of the material surface to promote osteogenesis. When biomaterials are implanted in the human body, immune cells are actively recruited to the material surface and induce a local inflammatory response. This inflammation-driven process can be manipulated by altering the biomaterial's properties, subsequently initiating osteogenic and osteoclast processes, with either positive or negative effects on osseointegration. Therefore, it is critical to select an implantable biomaterial with the ability to modulate the host immune response to create a favorable local osteogenic microenvironment.

[0003] Among all immune cells, macrophages have attracted much attention as key effector cells that regulate inflammatory responses. Once biomaterials are implanted in the body, monocytes in the host immune system adhere to the surface of the material and differentiate into macrophages. Cytokines secreted by macrophages recruit other inflammatory cells and initiate immune responses and subsequent osteoblastic or osteoclastogenic processes. In addition, the surface properties of biomaterials, such as surface morphology and composition, can induce macrophage polarization to the M1 or M2 phase. M1 phase macrophages are pro-inflammatory phenotypes that secrete iNOS, IL-1β, IL-6, and TNF-α, leading to osteoclastogenesis; in contrast, M2 phase macrophages are anti-inflammatory phenotypes that can secrete IL-4, IL-10, TGF-β1, and Arg-1, and can produce VEGF and BMP-2, which promote angiogenesis and osteogenesis through vascular endothelial cells and bone marrow mesenchymal stem cells, respectively, ultimately promoting bone regeneration. Considering the high plasticity of macrophages, new strategies for osteoimmunomodulatory biomaterials can be developed to regulate the secretion of osteoblast factors by macrophages, thereby inducing a local favorable osteoimmune environment to facilitate osteogenesis.

[0004] To date, titanium has been considered a good dental implantable biomaterial due to its excellent mechanical strength, biocompatibility and corrosion resistance. However, titanium is bioinert and lacks significant bioactivity when implanted in vivo. In fact, titanium implants only mechanically bond with the surrounding bone tissue and cannot fully mobilize and stimulate the bioactivity of surrounding cells. Adverse immune responses to titanium and its alloys may lead to poor bone integration, implant loosening or premature failure. Therefore, changing the physicochemical properties of the titanium surface is an important step in achieving good bone integration. At present, in order to obtain the ideal physicochemical properties of biomaterials, functional modification of dental implant surfaces has received increasing attention, including physical and chemical pretreatment of the implant surface. Physical surface modification involves physical vapor deposition, ion beam implantation and photolithography; chemical methods are considered to be the most popular and effective methods for implant surface modification, including acid etching, peroxidation, alkali treatment, anodization, introduction of functional molecules by covalent cross-linking, chemical vapor deposition and hydrothermal modification. However, these methods are inconvenient to apply because they involve complex detonation procedures, hazardous chemicals and large-scale manufacturing equipment. Therefore, a simpler surface modification method is urgently needed to introduce strontium ions into the titanium surface.

[0005] Lysozyme is a natural protein whose disulfide bonds can be broken by tri(2-carboxyethyl)phosphine (TCEP) under neutral conditions and undergo phase transition. The α-helix is ​​transformed into a β-fold to form an amyloid product, which can firmly attach to various substrates, giving the substrate surface more charges and functional groups such as amino, carboxyl and hydroxyl groups. The use of phase-changing lysozyme (PTL) to modify the surface of metal materials is a promising technology. Therefore, it is urgent to obtain a strontium-titanium-based bone biomaterial with bone immunomodulatory properties and a method thereof using lysozyme. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a strontium-injected titanium-based bone biomaterial and a preparation method and application thereof. The strontium-injected titanium-based bone biomaterial has good bone immune regulation properties and enhances the ability of bone regeneration.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a strontium-injected titanium-based bone biomaterial, comprising the following steps:

[0009] (1) polishing, cleaning and sterilizing the titanium sheet to obtain a sterile titanium sheet;

[0010] (2) mixing the lysozyme solution with strontium acetate to obtain a strontium-doped lysozyme solution;

[0011] (3) mixing the TCEP buffer solution with the strontium-doped lysozyme solution to obtain a strontium-doped lysozyme coating;

[0012] (4) coating the strontium-doped lysozyme on the surface of a sterile titanium sheet for reaction, washing with a PBS buffer solution, and vacuum drying to obtain a dried strontium-injected titanium-based bone biomaterial.

[0013] Preferably, in step (2), the concentration of the lysozyme is 1.5-2.5 mg / mL; the concentration of the strontium acetate is 1-3 mg / mL; and the volume ratio of the lysozyme to the strontium acetate is 1:1.

[0014] Preferably, in step (3), the concentration of the TCEP buffer is 45-55 nM, the pH value of the TCEP buffer is 5-6, and the volume ratio of the TCEP buffer to the strontium-doped lysozyme solution is 1:1.

[0015] Preferably, the surface shape of the strontium-injected titanium-based bone biomaterial is a necklace-shaped fiber mesh structure, and the diameter of each spherical particle in the necklace-shaped fiber mesh structure is 0.5 to 1 micron.

[0016] The present invention also provides a strontium-injected titanium-based bone biomaterial obtained according to the above preparation method.

[0017] The present invention also provides an implant material for promoting bone regeneration, the implant material comprising the above-mentioned strontium-injected titanium-based bone biomaterial and macrophage conditioned medium; the preparation method of the macrophage conditioned medium comprises: inoculating macrophages into the above-mentioned strontium-injected titanium-based bone biomaterial, collecting the supernatant after culturing for 4 days, and obtaining the macrophage conditioned medium.

[0018] The present invention also provides a use of the above strontium-injected titanium-based bone biomaterial or implant material in the preparation of a product with bone immune regulation performance.

[0019] Preferably, the strontium-injected titanium-based bone biomaterial can promote the expression of anti-inflammatory factors, promote the expression of bone healing-related factors and promote the M2 phase differentiation of macrophages; the anti-inflammatory factors include IL-1ra and / or IL-10, and the bone healing-related factors include VEGF and / or BMP-2.

[0020] The present invention also provides a use of the strontium-injected titanium-based bone biomaterial or implant material in the preparation of a product promoting bone regeneration.

[0021] Preferably, the implant material promotes the expression of osteogenesis-related genes, and the osteogenesis-related genes include one or more of Runx2, BMP-2, ALP, COLI, OCN and OPN. Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a strontium-injected titanium-based bone biomaterial and its preparation method and application. The present invention constructs a Sr@PTL coating on the titanium surface through the chelation of phase-transition lysozyme and strontium ions. The strontium-injected titanium-based bone biomaterial can continuously release strontium ions, has a good inflammation inhibition effect, can induce the polarization of the M2 phase of macrophages cultured on its surface, promote macrophages to secrete bone healing-related factors, regulate the local inflammatory environment, and shape an immune microenvironment conducive to osteogenesis by regulating the differentiation of the M2 phase of macrophages, thereby promoting bone regeneration, and also has good biocompatibility. Therefore, the present invention provides a new idea for the surface functionalization of implantable biomaterials. At the same time, the preparation method of the present invention is simple to operate, low in cost, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 SEM images of different samples;

[0024] Figure 2 Figures 1 and 2 are elemental analysis results of different samples. a is the elemental analysis result of the Ti sample group, b is the elemental analysis result of the PTL group, and c is the elemental analysis result of the Sr@PTL group.

[0025] Figure 3 is the in vitro release curve of Sr@PTL;

[0026] Figure 4 The figure shows the flow cytometry results of macrophage polarization in different sample groups;

[0027] Figure 5 Immunofluorescence images of macrophage polarization in different sample groups;

[0028] Figure 6 A is the expression of related factors after different samples were treated with macrophages, A is the expression result of anti-inflammatory related factors after different sample groups were treated with macrophages, and B is the electrophoresis of related healing factors after different sample groups were treated with macrophages;

[0029] Figure 7 This is a comparison chart of the expression of osteogenesis-related genes in different sample groups;

[0030] Figure 8 Micro-computed tomography images of femoral tissue after treatment for different sample groups;

[0031] Fig. 9 HE staining results of femur specimens after treatment of different sample groups;

[0032] Fig.10 The phenotypic results of macrophages in peripheral tissues after treatment with different sample groups;

[0033] Fig.11Goldner staining results of surrounding tissues after treatment in different sample groups;

[0034] Fig.12 Shown are the results of Runx2 immunohistochemical staining after different sample treatments. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a strontium-injected titanium-based bone biomaterial, comprising the following steps:

[0036] (1) polishing, cleaning and sterilizing the titanium sheet to obtain a sterile titanium sheet;

[0037] (2) mixing the lysozyme solution with strontium acetate to obtain a strontium-doped lysozyme solution;

[0038] (3) mixing the TCEP buffer solution with the strontium-doped lysozyme solution to obtain a strontium-doped lysozyme coating;

[0039] (4) coating the strontium-doped lysozyme on the surface of a sterile titanium sheet for reaction, washing with a PBS buffer solution, and vacuum drying to obtain a dried strontium-injected titanium-based bone biomaterial.

[0040] In the present invention, a titanium sheet is polished, cleaned and sterilized to obtain a sterile titanium sheet. The titanium sheet is preferably a titanium sheet with a diameter of 8 to 12 mm and a thickness of 0.5 to 1.5 mm, and the polishing method is preferably to polish with silicon carbide sandpaper of 400 mesh, 800 mesh and 1200 mesh in sequence. The polished titanium sheet is cleaned, and the solvent for the cleaning is preferably to clean in acetone, anhydrous ethanol and water in sequence. The cleaning method is preferably 195W ultrasonic cleaning for 25 to 35 minutes. After cleaning, the cleaned titanium sheet is sterilized, such as by high pressure sterilization at 120°C for 1 hour to obtain a sterile titanium sheet.

[0041] In the present invention, after obtaining the sterile titanium sheet, the lysozyme solution is mixed with strontium acetate to obtain a strontium-doped lysozyme solution. The concentration of the lysozyme is preferably 1.5 to 2.5 mg / mL, more preferably 1.8 to 2.3 mg / mL; the concentration of the strontium acetate is preferably 1 to 3 mg / mL, more preferably 1.5 to 2.5 mg / mL; the volume ratio of the lysozyme to strontium acetate is preferably 1:1. The present invention does not specifically limit the mixing method, and methods known in the art may be used, such as vortexing, shaking or stirring.

[0042] In the present invention, a TCEP buffer is mixed with the strontium-doped lysozyme solution to obtain a strontium-doped lysozyme coating. The concentration of the TCEP buffer is preferably 45 to 55 nM, more preferably 46 to 52 nM, the pH value of the TCEP buffer is preferably 5 to 6, and the volume ratio of the TCEP buffer to the strontium-doped lysozyme solution is preferably 1:1. The present invention does not specifically limit the mixing method, and methods known in the art can be used, such as vortexing, shaking or stirring.

[0043] In the present invention, strontium-doped lysozyme is coated on the surface of a sterile titanium sheet for reaction, and after being rinsed with PBS buffer, vacuum drying is performed to obtain a dried strontium-injected titanium-based bone biomaterial. The surface shape of the strontium-injected titanium-based bone biomaterial is a necklace-shaped fiber mesh structure, and the diameter of each spherical particle in the necklace-shaped fiber mesh structure is 0.5 to 1 micron. The reaction time is preferably 1.5 to 2.5 hours, and the reaction temperature is preferably 35 to 40°C. The PBS buffer used in the present invention is purchased from Solebow Technology Co., Ltd.

[0044] The present invention also provides a strontium-injected titanium-based bone biomaterial obtained according to the above preparation method.

[0045] The present invention also provides an implant material for promoting bone regeneration, the implant material comprising the above-mentioned strontium-injected titanium-based bone biomaterial and macrophage conditioned medium; the preparation method of the macrophage conditioned medium comprises: inoculating macrophages in the above-mentioned strontium-injected titanium-based bone biomaterial, collecting the supernatant after culturing for 4 days, and obtaining macrophage conditioned medium. As a preferred embodiment, macrophages are inoculated in the above-mentioned strontium-injected titanium-based bone biomaterial to obtain macrophages inoculated in the strontium-injected titanium-based bone biomaterial, and then the macrophages inoculated in the strontium-injected titanium-based bone biomaterial are cultured in a fresh DMEM medium containing 10% FBS, and the supernatant is collected after culturing for 4 days to obtain macrophage conditioned medium (CM). The culture conditions are preferably cultured at 37°C and 5% CO2. The present invention prepares CM by culturing macrophages on different materials, and applies them to BMSCs cultured in vitro to simulate the inflammatory microenvironment after the biomaterial is implanted in the body. Adhesion and proliferation are prerequisites for cell differentiation and can also be used to evaluate the cytotoxicity of biomaterials. The present invention found that after BMSCs were cultured in CM containing Sr@PTL group samples, they showed good proliferation and adhesion over time, indicating that Sr@PTL has good biocompatibility. The present invention has no special restrictions on the source of DMEM culture medium, and commercially available products in the art can be used.

[0046] The present invention also provides a use of the above strontium-injected titanium-based bone biomaterial or implant material in the preparation of a product with bone immune regulation performance.

[0047] In the present invention, the strontium-injected titanium-based bone biomaterial can promote the expression of anti-inflammatory factors, promote the expression of bone healing-related factors and promote the M2 phase differentiation of macrophages; the anti-inflammatory factors include IL-1ra and / or IL-10, and the bone healing-related factors include VEGF and / or BMP-2.

[0048] The present invention also provides a use of the strontium-injected titanium-based bone biomaterial or implant material in the preparation of a product promoting bone regeneration.

[0049] In the present invention, osteoblast differentiation is divided into three main biological periods: cell proliferation, cell maturation and extracellular matrix mineralization. In order to detect the osteogenic differentiation of BMSCs in the co-culture system, the expression levels of osteogenic-related genes Runx2, BMP-2, ColⅠ, ALP, OCN, and OPN in BMSCs were evaluated by RT-PCR. Runx2 is the most upstream transcription factor required for osteoblast differentiation and begins to express in the early stage of osteogenic differentiation; BMP-2 is a member of the TGF-β superfamily, which can promote the osteogenic differentiation of BMSCs by activating the BMP2 / Smad / Runx2 signaling pathway; ColⅠ is expressed in the early stage of cell proliferation and extracellular matrix synthesis; ALP is expressed in the late proliferation stage of extracellular matrix maturation; OCN and OPN are expressed in the third stage of extracellular matrix mineralization. The present invention has found that the implant material promotes the expression of osteogenic-related genes, and the osteogenic-related genes include one or more of Runx2, BMP-2, ALP, COL I, OCN and OPN. The strontium-infused titanium-based bone biomaterial promotes new bone formation and macrophage M2 phase differentiation, shapes an immune microenvironment that is conducive to osteogenesis, and further promotes bone integration.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0051] In the following examples, statistical analysis of the present invention: each experiment was repeated at least 3 times, all data were expressed as mean ± standard deviation, and t-test and variance analysis were performed using SPSS 22.0 statistical software. When p < 0.05, it was considered statistically significant, and p < 0.01 was considered a very significant statistical difference.

[0052] The lysozyme was purchased from Sigma, HEPES was purchased from Beijing Solarbio, TCEP was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd., strontium acetate powder was purchased from Sigma, and PBS buffer was purchased from Beijing Solarbio.

[0053] Example 1

[0054] 1.1 A strontium-injected titanium-based bone biomaterial, the preparation method of the bone biomaterial is as follows:

[0055] (1) Preparation of required solution:

[0056] Preparation of 2 mg / mL lysozyme solution: Dissolve 20 mg lysozyme in 10 mL of 10 mM HEPES buffer and adjust the pH to 7.4.

[0057] Preparation of 50 nM TCEP buffer: weigh 7.14 mg TCEP, dissolve it in 500 mL 10 mM HEPES buffer, and adjust the pH value to 7.4 with NaOH.

[0058] Preparation of 2 mg / mL strontium acetate: Weigh 20 mg of strontium acetate and dissolve it in 10 mL of PBS buffer.

[0059] (2) A titanium sheet with a diameter of 10 mm and a thickness of 1 mm was polished with 400-mesh, 800-mesh and 1200-mesh silicon carbide (SiC) sandpaper, respectively. The polished titanium sheet was then cleaned in acetone, anhydrous ethanol and deionized water with 195 W ultrasonic waves for 30 min, respectively, and sterilized in a high-pressure steam sterilizer at 120 ° C for 1 h to obtain a sterile titanium sheet.

[0060] (3) adding an equal volume of 2 mg / mL strontium acetate to the 2 mg / mL lysozyme solution to obtain a strontium-doped lysozyme solution;

[0061] (4) mixing a 50 nM TCEP buffer solution with a pH value of 5 to 6 and a strontium-doped lysozyme solution in a volume ratio of 1:1 to obtain a strontium-doped lysozyme coating;

[0062] (5) The strontium-doped lysozyme coating was quickly added to the surface of the sterile titanium sheet. After reacting for 2 h, the strontium-injected titanium-based bone biomaterial was taken out, and the remaining lysozyme product on the surface was rinsed with PBS buffer. A layer of strontium-doped lysozyme coating was modified on the sterile titanium surface, and then vacuum dried to obtain the dried strontium-injected titanium-based bone biomaterial, namely the Sr@PTL group, also known as the Ti-Ly-Sr group.

[0063] 1.2 Preparation of control samples

[0064] (1) Preparation of a sterile titanium sheet: A titanium sheet with a diameter of 10 mm and a thickness of 1 mm was polished with 400-mesh, 800-mesh and 1200-mesh silicon carbide (SiC) sandpaper, respectively. The polished titanium sheet was then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min, respectively, and sterilized at 120° C. for 1 h using a high-pressure steam sterilizer to obtain a sterile titanium sheet, i.e., Ti group.

[0065] (2) Preparation of a PTL-treated titanium sheet:

[0066] S1. Preparation of required solution:

[0067] Preparation of 2 mg / mL lysozyme solution: Dissolve 20 mg lysozyme in 10 mL of 10 mM HEPES buffer and adjust the pH to 7.4.

[0068] Preparation of 50 nM TCEP buffer: weigh 7.14 mg TCEP, dissolve it in 500 mL 10 mM HEPES buffer, and adjust the pH value to 7.4 with NaOH.

[0069] S2. A titanium sheet with a diameter of 10 mm and a thickness of 1 mm was polished with 400-mesh, 800-mesh and 1200-mesh silicon carbide (SiC) sandpaper in sequence. The polished titanium sheet was then ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min respectively, and sterilized at 120°C for 1 h using a high-pressure steam sterilizer to obtain a sterile titanium sheet.

[0070] S3, mixing a 50 nM TCEP buffer having a pH value of 5 to 6 and a 2 mg / mL lysozyme solution in a volume ratio of 1:1 to obtain a lysozyme coating;

[0071] S4. Rapidly add lysozyme coating to the surface of the sterile titanium sheet. After reacting at 37°C for 2 hours, take out the lysozyme-coated titanium sheet, rinse the remaining lysozyme product on the surface with PBS buffer, modify a layer of lysozyme coating on the sterile titanium surface, and then vacuum dry to obtain a dried lysozyme-coated titanium sheet, namely the PTL group, also known as the Ti-Ly group.

[0072] 1.3 Sample surface morphology observation and element analysis

[0073] (1) Scanning electron microscopy (SEM)

[0074] The surfaces of Ti, PTL, and Sr@PTL samples were measured as described above, and their microscopic morphologies were observed.

[0075] Figure 1 The results showed that the surface of the unmodified sterile titanium sheet was flat, with scratches left by SiC sandpaper polishing. The titanium sheet modified with PTL coating showed a necklace-like microfiber network structure, in which the diameter of the spherical particles constituting the fiber network was 0.5-1 μm, while the strontium-injected titanium-based bone biomaterial did not destroy the above structure of PTL. The surface shape of the strontium-injected titanium-based bone biomaterial was a necklace-like fiber network structure, in which the diameter of each spherical particle in the necklace-like fiber network structure was 0.5-1 μm.

[0076] (2) X-ray photoelectron spectroscopy (XPS)

[0077] XPS was used to analyze the surface elements of Ti, PTL and Sr@PTL samples.

[0078] Figure 2 The results show that only Ti element exists on the surface of the unmodified Ti group sample. Compared with the Ti group, the surface of the PTL group is rich in sulfur, phosphorus and nitrogen. The appearance of these three elements indicates that the PTL coating successfully covers the Ti surface. In addition to the sulfur, phosphorus and nitrogen elements of the PTL coating, the surface of the PTL-SR group also contains Sr, indicating that Sr is successfully introduced into the PTL coating.

[0079] 1.4Sr release detection

[0080] In order to analyze the release behavior of Sr, the samples of the Sr@PTL group were immersed in 10 mL PBS buffer and placed in a constant temperature shaker (37 ° C, 70 rpm / min) to simulate the blood circulation environment in vivo. The soaking liquid of each sample was collected on the 1st, 2nd, 3rd, 4th, 5th, and 6th days, and the samples were soaked again with 10 mL of fresh PBS. The release amount of Sr in the collected liquid was detected by inductively coupled plasma emission spectrometry (ICP-AES), and the in vitro release curve of Sr@PTL was drawn.

[0081] Figure 3 The results show that within a certain period of time, the amount of Sr ions released increases with time.

[0082] In summary, the present invention introduces Sr on the PTL coating through chelation to achieve surface functional modification of the titanium substrate, and a series of characterization analyses are performed to verify the successful construction of the Sr@PTL coating. SEM images show that the strontium-doped PTL coating is uniformly deposited on the surface of the titanium substrate. XPS confirms the presence of sulfur, phosphorus and nitrogen on the Ti surface after PTL modification, indicating that the PTL coating successfully gives the Ti substrate functional groups such as amino, carboxyl and hydroxyl. After the introduction of Sr, the presence of strontium was observed on the surface of the Ti sheet, thereby successfully obtaining the PTL-Sr coating on the Ti sheet. In addition, the results of ICP-AES show that Sr has a stable and lasting release, proving that the PTL coating can be used as an active ion release system to ensure the appropriate concentration of Sr in the local bone microenvironment. Therefore, this experiment successfully prepared a PTL coating on the surface of the Ti substrate, and constructed a Sr@PTL coating through chelation to achieve surface functional modification of titanium.

[0083] 2.1 Effects of Sr@PTL on macrophage polarization and immune response

[0084] 2.1.1 Cell culture

[0085] RAW264.7 cells were cultured in a DMEM high-glucose medium containing 10% FBS and 1% (v / v) penicillin / streptomycin at 37°C and 5% CO2 incubator. The culture medium was changed every 3 days. When the cell density reached about 80%, the cell suspension was gently scraped and separated using a cell scraper, and the cell suspension was transferred to a 15mL centrifuge tube, centrifuged at 800rpm for 5min, the supernatant was discarded, and the cell clumps were blown with an appropriate amount of fresh culture medium to resuspend them. Finally, the cell suspension was transferred to a sterile culture bottle, the culture medium was supplemented, the cells were shaken by the cross method, and then placed in a 7°C, 5% CO2 incubator for continued culture. The 3rd to 6th generation cells were taken for in vitro experiments.

[0086] 2.1.2 Flow cytometry

[0087] Flow cytometry was used to detect the expression of macrophage surface markers M1 (CCR7) and M2 (CD206). Briefly, samples of Ti, PTL, and Sr@PTL groups were placed in 24-well plates and then 1×10 4 RAW264.7 cells in logarithmic growth phase were inoculated on the surface of different samples in 24-well plates at a density of 100 μl / well. After 4 days of culture, RAW264.7 cells were gently scraped and collected, the cell suspension was centrifuged at 1200 rpm for 4 min at 4 ° C, and the cells were resuspended in PBS containing 1% BSA and incubated at room temperature for 30 min to block Fc receptors. Then, anti-mouse CCR7 and CD206 antibodies were added and incubated at 4 ° C for 30 min, and then incubated with Dylight488-anti-goat and AlexaFluor488-anti-rabbit secondary antibodies at 4 ° C for 30 min in the dark. The cells were washed 3 times with 1% BSA, transferred to fluorescence-activated cell sorting tubes (200 μL / tube), and the expression of RAW264.7 cell surface markers was detected by flow cytometry.

[0088] Figure 4 The results showed that the trend of M1 phenotype (CCR7) was Ti (37.29) > PTL (28.47) > Sr@PTL (19.57). The trend of M2 phenotype (CD206) was Sr@PTL (41.36) > PTL (38.14) > Ti (22.49).

[0089] 2.1.3 Immunofluorescence detection of macrophage polarization

[0090] The Ti, PTL, and Sr@PTL samples were placed in a 24-well plate and then 4RAW264.7 cells in logarithmic growth phase were seeded on the surface of different samples in 24-well plates at a density of 100 cells / well. After 4 days of culture, RAW264.7 cells were gently scraped and collected, and the expression of macrophage surface markers M1 (CCR7) and M2 (CD206) was marked.

[0091] Figure 5 The results showed that the Sr@PTL group also had high M2 expression, which further confirmed the flow cytometry results. Compared with the pure Ti group, both the PTL and Sr@PTL groups induced a higher proportion of RAW264.7 cells to express the M2 phenotype marker CD206.

[0092] 2.1.4 Detection of inflammatory factor gene expression after each sample was treated with RAW264.7 cells

[0093] RT-PCR was used to detect the gene expression of TNF-α, IL-1β, IL-6, IL-1ra and IL-10 in the culture medium of RAW264.7 cells. The Ti, PTL and Sr@PTL group samples were placed in a 24-well plate and then 1×10 4 RAW264.7 cells in logarithmic growth phase were inoculated on the surface of different samples in 24-well plates at a density of 10 cells / well. After 4 days of culture, the culture supernatant of RAW264.7 cells was collected to measure the expression of the above inflammatory factors.

[0094] 2.1.5 Detection of RAW264.7 cell healing-related factors on the surface of each sample

[0095] Western blot was used to detect the protein expression of BMP-2 and VEGF in RAW 264.7 cells. The samples of Ti, PTL, and PTL-Sr groups were placed in 24-well plates and then 1×10 4RAW264.7 cells in logarithmic growth phase were inoculated on the surface of different samples in 24-well plates at a density of 100 / well. After 4 days of culture, cells were lysed on ice for 30 minutes using RIPA protein lysis buffer containing PMSF protease inhibitor, cell lysate was collected, centrifuged at 14000rpm for 15 minutes at 4℃, and the supernatant containing protein was transferred to a new EP tube. 5× denaturation buffer was added to the protein sample at a volume ratio of 1:4, and the protein was denatured by boiling at 100℃ for 5 minutes. The protein sample was stored at -80℃ for use. The total protein level was quantitatively analyzed using a BCA kit. 15 mg of protein was separated by SDS-PAGE gel and transferred to a nitrocellulose membrane. After blocking with TBST buffer containing 5% (w / v) skim milk for 1 hour, it was incubated with primary antibodies for BMP-2, VEGF and β-actin at 4℃ overnight. After washing with TBST buffer three times, it was incubated with goat anti-rabbit secondary antibody labeled with horseradish peroxidase at room temperature for 1 hour. The protein bands were displayed using an ECL kit, β-actin was used as an internal reference, and the protein bands were quantitatively analyzed using Image Pro Plus software.

[0096] Figure 6 The results showed that compared with the pure Ti and PTL groups, the expression of anti-inflammatory cytokines IL-1ra and IL-10 in the Sr@PTL group was significantly upregulated (see Figure 6 Compared with the pure Ti and PTL groups, the expressions of BMP-2 and VEGF, proteins that promote healing, in the Sr@PTL group were also significantly upregulated (see Figure 6 B). Based on the above results, Sr@PTL coating can create the most favorable immune microenvironment by regulating the polarization of macrophages, enhance the osteogenesis, and lay the foundation for subsequent bone integration.

[0097] 2.1.7 Preparation of macrophage conditioned medium (CM)

[0098] In order to study the osteoimmunomodulatory effect of Sr@PTL coating, RAW264.7 cells were inoculated on different samples (pure Ti, PTL, Sr@PTL) at a density of 1×10 4 The cells were cultured in a 24-well plate at a concentration of 100 cells / well in fresh DMEM medium containing 10% FBS. After 4 days, the supernatant was collected and mixed with fresh DMEM containing 5% FBS at a ratio of 1:1 to prepare CM, which was stored at 4°C for subsequent use.

[0099] 3.1 Effect of Sr@PTL on the behavior of bone marrow mesenchymal stem cells

[0100] 3.1.1 Osteogenesis-related gene detection

[0101] BMSCs were cultured at a rate of 1×10 4The density of cells / well was inoculated in a 24-well plate containing different samples (Ti, PTL, Sr@PTL), and 1 mL of CM was added for 4 days to detect the expression of osteogenic marker genes: Runx2, BMP-2, COLⅠ, ALP, OCN, OPN, and the housekeeping gene GAPDH was used as a reference. At the same time, the same volume of DMEM medium containing 5% FBS was added as a blank control (i.e., control group). The primer sequences of the target genes are shown in Table 1.

[0102] Table 1 Primer sequences of osteogenic marker genes

[0103]

[0104]

[0105] The RT-PCR steps are as follows:

[0106] S1. Extraction of total RNA from cells

[0107] (1) Discard the old culture medium and wash with PBS three times. Add 200 μL TRIzol to each well and pipette thoroughly to lyse the cells. After standing for 5 min, collect the cell lysate and transfer it to an EP tube;

[0108] (2) Add 40 μL of chloroform to each sample and shake the EP tube thoroughly to mix TRIzol and chloroform. After standing for 2 minutes, the sample can be seen to be separated into layers: the pink lower layer is TRIzol, and the colorless and transparent upper layer is chloroform;

[0109] (3) Centrifuge at 12000 rpm and 4°C for 15 min. After centrifugation, the sample is divided into three layers: the upper colorless transparent layer is the chloroform solution that dissolves RNA, the middle white emulsified layer is protein and cell debris, and the lower pink layer is TRIzol. Carefully transfer the upper colorless solution to a new EP tube;

[0110] (4) Add an equal volume of isopropanol to the colorless solution transferred from the previous step, mix thoroughly, and centrifuge at 12,000 rpm and 4°C for 10 min. After centrifugation, a white precipitate can be seen at the bottom of the EP tube;

[0111] (5) Discard the supernatant and add 1 mL of 70% ethanol to wash the residual isopropanol in the tube. Centrifuge at 7500 rpm and 4°C for 5 min. Discard the supernatant and centrifuge again at 7500 rpm and 4°C for 5 min. After the centrifugation, carefully remove the residual ethanol solution. Open the EP tube and dry it at room temperature until the ethanol is completely evaporated. At this time, the RNA precipitate at the bottom changes from white to colorless and transparent;

[0112] (6) Add 20 μL of 0.1% DEPC water to each tube to dissolve the RNA precipitate, aspirate 1 μL of RNA aqueous solution, and measure the RNA content using a UV spectrophotometer.

[0113] S2. RNA reverse transcription to synthesize cDNA

[0114] According to the RNA content measured in the previous step, aspirate the aqueous solution containing 1 μg RNA. According to the manufacturer's instructions, use a reverse transcription kit to react at 37°C for 15 min and 85°C for 5 s to reverse transcribe RNA and synthesize cDNA;

[0115] S3. Real-time quantitative PCR reaction

[0116] Add 20 μL of PCR reaction solution to the eight-tube concatenation and place it in a PCR instrument. Set the activation temperature to 95°C for 2 min, then perform 40 cycles at this temperature for 5 s, followed by 30 cycles at 60°C. -ΔΔCt The expression levels of target genes were detected by GAPDH method and normalized by GAPDH value.

[0117] Figure 7 The results showed that the expression of osteogenic-related genes in the Sr@PTL group was significantly upregulated, and the Sr@PTL group had the strongest upregulation effect on the expression of osteogenic-related markers, which could effectively promote the osteogenic differentiation of BMSCs by regulating macrophage polarization.

[0118] 4.1 Detection of bone immune regulation performance of Sr@PTL in vivo

[0119] 4.1.1 Establishment of bilateral lateral femoral condyle implantation model in rats

[0120] Twelve 13-week-old male Wistar rats weighing 300-350 g were used in the experiment, provided by the Experimental Animal Center of Tianjin Medical University. All rats were kept under standard conditions, with a room temperature of 23±2°C, a humidity of 55±10%, a 12 / 12-hour day and night cycle, and free access to food and water. Before the experiment, all rats were kept for one week to adapt to the environment.

[0121] The rats after acclimatization were randomly divided into 3 groups, namely Ti group, PTL group and Sr@PTL group, with 4 rats in each group. The flat lateral surface of bilateral femoral condyles was selected as the surgical site. After general anesthesia by intraperitoneal injection of 10% chloral hydrate (0.3mL / 100g), the skin of bilateral hind limbs was prepared, iodine disinfection was performed, and 2% lidocaine was injected into the surgical site for local anesthesia. The lateral femoral condyle was exposed by incision of skin and muscle tissue. Under a large amount of sterile saline flushing, a 1.5×5mm bone defect was prepared with an electric dental drill driven by a 1.5mm drill bit. Ti, PTL and Sr@PTL samples were placed perpendicular to the long axis of the femur on the bilateral femoral condyles, and then the tissues were sutured in layers. The whole operation strictly followed the principle of sterility. Gentomycin (5mg / kg) was injected immediately after surgery to prevent infection for 3 consecutive days.

[0122] Six rats were killed by intraperitoneal injection of an overdose of chloral hydrate at 1 and 4 weeks after implantation, and the femurs with implants were removed and fixed in 10% neutral formalin buffer for subsequent imaging and histological experiments.

[0123] 4.1.2 Imaging observation using micro-computed tomography (μ-CT)

[0124] The femoral tissue was analyzed by μ-CT 4 weeks after the implantation of the sample under the conditions of 1 mm aluminum filter, 85 kV voltage, and 200 μA current. The sample and bone tissue were reconstructed in three dimensions using NRecon (version 1.7.4.2) software, and then the reconstructed images were analyzed using CTAnalyzer (version 1.18.8.0) software to measure the bone volume / total volume (BV / TV), bone density (BMD), trabecular thickness (Tb.Th), trabecular number (Tb.N), and trabecular spacing (Tb.Sp) of the bone tissue around the sample, and expressed as mean ± standard deviation.

[0125] Figure 8 The results showed that the new bone tissue around the implants in the pure Ti group and the PTL group was discontinuous, and the new bone voids around the implants in the Sr@PTL group were relatively small.

[0126] 4.1.3 Histological analysis

[0127] S1. HE staining: Femoral specimens implanted for 1 and 4 weeks were taken for HE staining. Fixed tissue samples were first decalcified in 17% EDTA for 6 weeks, and the decalcification solution was changed every 3 days. The decalcified tissues were dehydrated in 50%, 75%, 85%, 95% and 100% ethanol solutions, respectively, and then embedded in paraffin blocks. A tissue slicer was used to cut 5 μm slices perpendicular to the long axis of the implant. After dewaxing with xylene and gradient decreasing from ethanol to water, some slices were stained with hematoxylin-eosin.

[0128] Fig. 9 The results showed that osteoid was generated on the surface of the Sr@PTL group material after 7 days, while the blank titanium group had fibrous tissue; new bone appeared on the surface of the Sr@PTL group after 28 days.

[0129] S2. Immunofluorescence staining: In order to further verify the phenotype of macrophages in the peri-implant tissue, the remaining paraffin sections made from the femoral specimens implanted for 1 week were subjected to DAPI, CD206, and CCR7 immunofluorescence staining. The steps are as follows:

[0130] (1) Dewaxing the sections into water;

[0131] (2) Antigen retrieval was performed by incubating with 0.5% trypsin at room temperature for 20 min and then washing with PBS for 5 min, three times;

[0132] (3) Block with 5% skim milk at room temperature for 30 min and wash with PBS for 5 min, three times;

[0133] (4) Incubate with rabbit anti-rat Arg-1 and rabbit anti-rat iNOS primary antibodies at a dilution of 1:100 at room temperature for 60 min, and wash with PBS for 5 min, three times;

[0134] (5) Incubate with goat anti-rabbit IgG secondary antibody at room temperature for 30 min and wash with PBS for 5 min, three times;

[0135] (6) Seal the slides with anti-fluorescence attenuation mounting medium containing DAPI;

[0136] (7) Images were acquired using a confocal laser scanning microscope.

[0137] Fig.10 The results showed that compared with the Ti group and PTL group, the M2 polarization of the Sr@PTL group was obvious.

[0138] S3, Goldner trichrome staining: In order to observe the new bone formation around the implant, the tissue 4 weeks after implantation was embedded in paraffin and sliced ​​as described above, and the tissue sections were stained with Goldner trichrome staining solution according to the instructions. This staining method is based on the principle that the molecular size of anionic dyes is related to tissue penetration, and can dye mineralized and mature bone tissue green and osteoid orange-red.

[0139] Fig.11 The results showed that red represents new bone, Sr@PTL can be seen, the surrounding bone remodeling is active, and the new tissue on the surface has some red, representing osteoid. Compared with the Ti group and the PTL group, Sr@PTL promoted new bone formation.

[0140] S4. Immunohistochemical staining: To further evaluate the expression of osteogenic markers around the implants, Runx2 immunohistochemical staining was performed on tissue sections 4 weeks after implantation. The steps are as follows:

[0141] (1) Dewaxing the sections into water;

[0142] (2) Antigen retrieval was performed with citrate buffer (80°C, pH 6.5) for 10 min, and the samples were naturally cooled and air-dried at room temperature;

[0143] (3) Incubate with 3% hydrogen peroxide for 10 min to block endogenous peroxidase, and wash with PBS for 5 min, three times;

[0144] (4) 5% skim milk blocking for 30 min;

[0145] (5) Remove the blocking solution and incubate with anti-Runx2 (rabbit anti-rat) primary antibody at 4°C overnight;

[0146] (6) The slices were placed at room temperature for 30 min to rewarm;

[0147] (7) Dry the sections thoroughly, add secondary antibody, incubate at room temperature for 30 min, and wash with PBS for 5 min, three times;

[0148] (8) DAB was added for development, hematoxylin was used for counterstaining, and then the slides were washed with anhydrous ethanol and sealed with neutral gum;

[0149] (9) Use an optical microscope and imaging system to acquire slice images.

[0150] Fig.12 The results showed that Runx2 is an early osteogenesis indicator, and a large brown-stained area represents high Runx2 expression. The results showed that the expression of Runx2 in Sr@PTL was high compared with the Ti group and the PTL group.

[0151] In summary, according to the results of immunofluorescence staining, 7 days after implantation, the Sr@PTL group induced the polarization of most macrophages into the M2 phase and stimulated an environment conducive to bone immune regulation. In the second stage of bone integration, angiogenesis began, BMSCs were recruited to the surface of the implant, and differentiated into osteoblasts or osteoclasts under the stimulation of cytokines in the surrounding environment. μ-CT and Goldner trichrome staining images showed new bone formation around the implant. After 4 weeks of implantation, due to the formation of a good bone microenvironment locally, a large amount of new bone regeneration occurred in the Sr@PTL group, showing a higher bone density and bone mineralization. Immunohistochemical staining of the osteogenic-related protein Runx2 in the bone tissue around the implant also showed consistent results with μ-CT and Goldner trichrome staining.

[0152] Therefore, the Sr@PTL coating of the present invention can create a good bone immune microenvironment in vivo by inducing the polarization of macrophages to promote the differentiation of BMSCs towards osteoblasts, and finally achieve good bone integration between the implant and the host bone tissue.

[0153] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a strontium-injected titanium-based bone biomaterial, characterized in that: The following steps are involved: (1) polishing, cleaning and sterilizing the titanium sheet to obtain a sterile titanium sheet; (2) mixing the lysozyme solution with strontium acetate to obtain a strontium-doped lysozyme solution; (3) mixing the TCEP buffer solution with the strontium-doped lysozyme solution to obtain a strontium-doped lysozyme coating; (4) coating the strontium-doped lysozyme on the surface of a sterile titanium sheet for reaction, rinsing with PBS buffer, and vacuum drying to obtain a dried strontium-injected titanium-based bone biomaterial.

2. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the lysozyme is 1.5-2.5 mg / mL; the concentration of the strontium acetate is 1-3 mg / mL; and the volume ratio of the lysozyme to the strontium acetate is 1:

1.

3. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the TCEP buffer is 45-55 nM, the pH value of the TCEP buffer is 5-6, and the volume ratio of the TCEP buffer to the strontium-doped lysozyme solution is 1:

1.

4. The preparation method according to claim 1, characterized in that: The surface shape of the strontium-injected titanium-based bone biomaterial is a necklace-shaped fiber mesh structure, and the diameter of each spherical particle in the necklace-shaped fiber mesh structure is 0.5 to 1 micron.

5. A strontium-implanted titanium-based bone biomaterial obtained according to the preparation method according to any one of claims 1 to 4.

6. An implant material for promoting bone regeneration, characterized in that: The implant material comprises the strontium-injected titanium-based bone biomaterial according to claim 5 and macrophage conditioned medium; the method for preparing the macrophage conditioned medium comprises: inoculating macrophages into the strontium-injected titanium-based bone biomaterial according to claim 5, collecting the supernatant after culturing for 4 days, and obtaining the macrophage conditioned medium.

7. Use of the strontium-injected titanium-based bone biomaterial according to claim 5 or the implant material according to claim 6 in the preparation of a product with bone immunomodulatory properties.

8. The use according to claim 7, characterized in that: The strontium-injected titanium-based bone biomaterial can promote the expression of anti-inflammatory factors, promote the expression of bone healing-related factors and promote the M2 phase differentiation of macrophages; the anti-inflammatory factors include IL-1ra and / or IL-10, and the bone healing-related factors include VEGF and / or BMP-2.

9. Use of the strontium-injected titanium-based bone biomaterial according to claim 5 or the implant material according to claim 6 in the preparation of a product promoting bone regeneration.

10. The use according to claim 9, characterized in that: The implant material promotes the expression of osteogenesis-related genes, and the osteogenesis-related genes include one or more of Runx2, BMP-2, ALP, COLI, OCN and OPN.